Microbiology and Antibiotic Susceptibility Pattern in Congenital Nasolacrimal Duct Obstruction - Maneksha Velu; K. S. Aparna (Delhi Journal of Ophthalmology)
Purpose: To analyze the microbiological spectrum and antibiotic sensitivity in children with congenital nasolacrimal duct obstruction (CNLDO) and determine the empirical drug of choice. Methodology: A prospective study included 198 eyes of 170 patients aged 0–5 years with CNLDO, who were regurgitation on pressure over lacrimal sac positive. Conjunctival swabs after applying pressure over the lacrimal sac were sent for microbiology. Antibiotic susceptibility testing was done by Kirby–Bauer disc diffusion method. Results: 94.94% of samples were culture positive and 48.4% were Gram-positive. The most common Gram-positive and Gram-negative organisms isolated were Streptococcus pneumoniae and Haemophilus influenzae, respectively. Gram-positive organisms showed the highest sensitivity to chloramphenicol and Gram-negatives to amikacin. Both isolates were susceptible to ofloxacin and gatifloxacin. Eighty-seven eyes underwent probing with overall success rate of 83.91%. Conclusions: There was a Gram-positive predominance in CNLDO. Based on our results, fluoroquinolone drops are a good option in the treatment of cases with CNLDO.